Capturing the impact employees have on their coworkers and leaders: a holistic approach on health-specific support behavior from employees - Gosch, Nora; Schulte, Eva-Maria; Kauffeld, Simone (Frontiers in Psychology, 2023)
Support is a valuable resource for ensuring employee health in the workplace. However, research on health-specific support behavior (i.e., support specifically targeting concrete health aspects) has only concentrated on either leader behavior (e.g., healthy leadership styles) or support provided by employees for specific health issues (e.g., healthy eating or smoking cessation). Although the importance of employee health has been well established, the examination of a wider range of potential health-specific support behaviors from employees provided for their colleagues and leaders has been neglected. To understand employee health-specific support behavior, we adapted an existing health-oriented leadership questionnaire to cover support for colleagues (PeerCare) and their leaders (LeaderCare). Capturing the employee perspective with a sample of 347 employees, the results confirmed a delineation of health-oriented scales (factor, convergent, and discriminant validity). By testing health-specific support behavior processes at work, the positive effects of PeerCare on general health were demonstrated. Contrary to expectations, existing health effects are outweighed when leaders provide health-specific support behavior to their employees (StaffCare). However, the results imply that the health-specific support behavior practices of different actors reinforce each other: the effects of StaffCare and PeerCare enhance each other, and StaffCare has a strong influence on LeaderCare. Remarkably, SelfCare has a key role in this process. The open questions and implications regarding the effects of the different health-specific support behavior measurements are discussed.